Improvement of the Quality of Education - Abdurakhmonova Makhfuzakhan Mahammadsodikovna (Researchparks Publishing, 2023)
It is illuminated by the author that quality in education is not only a reflection of the result of the educational process, but also a system, a model that ensures the complex personal and social development of learners and allows them to contribute to the development of Science, Technology, Society, fully taking into account their needs.